Mencari Variabel-variabel Yang Mempengaruhi Sikap Mental Entrepreneural (Wirausaha)Pada Pemerintah Kabupaten Serdang Bedagai - Arfan Ikhsan (Media Riset Akuntansi, Auditing & Informasi, 2006)
This research try to find some variables that influence entrepreneurial mental attitude at government of Serdang Bedagai Regency. independent variable which considered in this research is hierarchy, formalizes, trust, mission, ethics and regulation barriers level. Those independent variables will be able to improve society satisfaction, reduction of level of bureaucracy and improvement of risking tendency. The data of this research collected from organization chart of Serdang Bedagai Regency. Amount of 68 responders participated in this research. Hereinafter this data processed by using multiple regression analysis. The result shows that formalizes, trust, mission, ethics and regulation barriers level have an effect significantly toward society satisfaction and also bureaucracy. Meanwhile risking tendency is significantly influenced by hierarchy, formalizes, mission and ethics.Key Words: hierarchy, formalizes, trust, mission, ethics and regulation barriers level